PLOT ANALYSIS OF SHORT STORY " FRIENDS FOREVER" BY ADITI DAS BHOWMIK - Ridho, Ahmad Syah (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2016)
This research has a purpose to understand structure of âfriends foreverâ short storyÂ Â  plot. Knowledge about structure of âfriends foreverâ plot is useful to increase readerâs appreciation. This research use a descriptive qualitative method. That allows the researcher to describe a phenomenon by presenting the facts in rich detail without attempting to interpret them. Qualitative research is done without give priority in numbers, but focus on the deep understanding to interaction between concepts.This structure describes aesthetic aspects. In analysis the data the researcher used structural hermeneutic by Paul Ricoeur. Proposed this theory emphasizes the importance of function in the structure of âfriends foreverâ short story.Â  Plot Short story friends foreverÂ  can be describe exposition, rising action, conflix, climax, rising action and resolution.The researches expectation can be useful for the readers in developing knowledge about plot as one of elements of fiction and can help the readers in understanding the story line of the âfriends foreverâ short story